Western Sahara: Africa’s last colony - martin, juan carlos gimeno (Tensões Mundiais, 2018)
This article aims to reveal the complicity of the international community with Moroccan colonialism in Western Sahara. Since 1987, the Moroccan wall separates the Saharawi people into two groups: one group lives under Moroccan occupation, the other lives in exile camps in Southern Algeria. It is a Bedouin village, nomadic, colonized by Spain, but has maintained a persistent anti-colonial resistance and struggle for self-determination.